Monitoring of food handlers and their influence on the preparation of ready-to-eat foods - Ochoa-Agudelo, Susana; Tobón-Ospina, Juliana; Fuentes-Vanegas, Mayra Alejandra; Durango-Zuleta, Mónica María (Universidad y Salud, 2024)
Introduction: Transmission of foodborne pathogens is related to inadequate sanitary conditions, which are derived from either the food preparation process or the person who prepares it. Food handlers are essential to preserve food innocuousness and protect consumer’s health. Objective: To evaluate demographic characteristics, hygiene practices, knowledge, work conditions and the presence of pathogenic microorganisms in food handlers at public school restaurants in Antioquia, Colombia. Materials and methods: The study evaluated 104 food handlers in a municipality in Antioquia. Demographic data and stool samples were collected to identify intestinal parasites, Salmonella spp., and Staphylococcus aureus. Results: The presence of intestinal parasites (e.g. Entamoeba Complex and Trichuris trichiura) was identified in 61% of female participants. Staphylococcus aureus was isolated from 49% of food handlers. Conclusion: Infection of food handler was confirmed, making them potential sources of food contamination. They are committed to their work and have the knowledge to preserve basic hygiene conditions. It is highlighted their importance and influence in adequate hygienic practices to minimize the risks of transmission, as well as the need for medical treatment and regular checkups of food handlers to counteract the risk to consumers.